How Does Environmental Inter-annual Variability Shape Aquatic Microbial Communities? A 40-Year Annual Record of Sedimentary DNA From a Boreal Lake (Nylandssjön, Sweden) - Capo, Eric; Rydberg, Johan; Tolu, Julie; Domaizon, Isabelle; Debroas, Didier; Bindler, Richard; Bigler, Christian (Frontiers in Ecology and Evolution, 2019)
To assess the sensitivity of lakes to anthropogenically-driven environmental changes (e.g., nutrient supply, climate change), it is necessary to first isolate the effects of between-year variability in weather conditions. This variability can strongly impact a lake’s biological community especially in boreal and arctic areas where snow phenology play an important role in controlling the input of terrestrial matter to the lake. Identifying the importance of this inherent variability is difficult without time series that span at least several decades. Here, we applied a molecular approach (metabarcoding on eukaryotic 18S rRNA genes and qPCR on cyanobacterial 16S rRNA genes) to sedimentary DNA (sed-DNA) to unravel the annual variability of microbial community in 40 years’ sediment record from the boreal lake Nylandssjön which preserve annually-laminated sediments. Our comparison between seasonal meteorological data, sediment inorganic geochemistry (X-ray fluorescence analyses) and organic biomarkers (pyrolysis-gas chromatography/mass spectrometry analyses), demonstrated that inter-annual variability strongly influence the sediment composition in Nylandssjön. Spring temperature, snow and ice phenology (e.g. the percentage of snow loss in spring, the timing of lake ice-off) were identified as important drivers for the inputs of terrestrial material to the lake, and were therefore also important for shaping the aquatic biological community. Main changes were detected in the late-80s/mid-90s and mid-2000s associated with increases in algal productivity (see from organic biomarkers), in total richness of the protistan community and in relative abundances of Chlorophyta, Dinophyceae as well as Cyanobacteria abundance. These changes could be linked to a decline in terrestrial inputs to the lake during the snow melt and run-off period, which in turn was driven by warmer winter temperatures. Even if our data shows that meteorological factors do affect the sediment composition, they only explain part of the variability. This is most likely a consequence of the high inter-annual variability in abiotic and biotic parameters highlighting the difficulty to draw firm conclusions concerning drivers of biological changes at an annual or sub-annual resolution even with the 40-year varved sediment record from Nylandssjön. Hence, it is necessary to have an even longer time perspective in order to reveal the full implications of climate change.